Prolonged severe acute respiratory syndrome of Corona Virus-2 positive with polymerase chain reaction: A case report - Linda Rosita; Rahma Yuantari; Budi Mulyono; Umi Solekhah Intansari; Ingesti Bilkis Zulfatina (Faculty of Medicine, Universitas Islam Indonesia, 2020)
COVID-19 continues to spread across the world, with more than 60 million confirmed cases in 220 countries. Since March 11, 2020, WHO announced the COVID-19 outbreak as a pandemic. Impacts caused by COVID-19 are not only on the health sector but also economic, social, and political sectors. In a diagnosing process, the SARS-CoV-2 PCR results for swab specimen are a gold standard in determining confirmed COVID-19 cases. Previously, 2 repeated results of negative SARS-CoV-2 PCR become criteria of being recovered from COVID-19. Therefore, based on the latest guidelines from the Indonesian Ministry of Health revised on July 13th 2020, patients with no symptoms, mild to moderate symptoms, and severe symptoms are declared to be recovered if the patients meet the requirements of finished periods of isolation based on a doctor’s assessment. Confirmed cases with severe or critical symptoms are specially declared with one negative result of the PCR test plus three days without showing any symptoms. This case study discussed a 52-years-old woman diagnosed with COVID-19. PCR test for this patient had been conducted 11 times during 64 days of treatment, and its results turned to be always positive, failing to fulfil the discharge criteria. Therefore, it needs to determine causes of prolonged positive PCR results and impacts of clinical condition of the patients, and prognosis of the patients.